Synthesis of ZnN nanostructures for gas sensing applications - Muhammad Kashif (School of Nano Electronic Engineering, 2013)
The objective of this research is to synthesize different ZnO nanostructures using low-cost sol-gel spin coating method for gas sensing applications.